PENGARUH ANTARA PENGELOLAAN KONFLIK DAN MOTIVASI KERJA DENGAN KOMITMEN ORGANISASI GURU SD NEGERI GUGUS 03 KECAMATAN TAMPAN KOTA PEKANBARU - Sasmarianto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
In accordance with the proposed hypothesis, the aim of this study was to determine the relationship between the variables: 1) Conflict management toward organizational commitment; 2) Motivation toward organizational commitment; 3) Conflict management and motivation together toward organizational commitment. This was achieved through the distribution of questionnaires to 72 teachers of the State Elementary School (SDN 03) Tampan, Pekanbaru, using a proportional stratified random sampling technique. A questionnaire, as the instrument in this study, was used to collect data on conflict management, motivation, and organizational commitment. The validity of the items was tested by using the Pearson Product Moment formula, and the reliability coefficient instrument was calculated by using Cronbach's alpha formula. The results showed that there was a positive relationship between conflict management and organizational commitment, with a correlation coefficient ry1=0.531 and the regression equation Y=42.439 + 0.542 X1. 2) There is a positive relationship between motivation and organizational commitment with the correlation coefficient ry2= 0.475 and the regression equation Y=45.023 + 0.448 X2. 3) There is a positive relationship between conflict management and motivation with organizational commitment and multiple correlation coefficient Ry1.2=0.607 and regression equation Y=28.450 + 0.434X1 + 0.308 X2. The results of this study are expected to be useful for the improvement and enhancement of organizational commitment in the State Elementary School (SDN 03) Kecamatan Tampan, Pekanbaru. This can be enhanced by conflict management and motivation improvement of teachers.